2018
DOI: 10.1097/dcr.0000000000001109
|View full text |Cite
|
Sign up to set email alerts
|

Histological Comparison of Cold versus Hot Snare Resections of the Colorectal Mucosa

Abstract: Hot resection caused damage to deeper layers involving more large vessels. This may explain the mechanism for the reduced incidence of hemorrhage after cold snare polypectomy. See Video Abstract at http://links.lww.com/DCR/A631.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
1
29
0
1
Order By: Relevance
“…Both adenomas and superficial adenocarcinomas are subject to endoscopic resection. Cold‐snare polypectomy (CSP) is becoming increasingly popular for the resection of adenomas; however, whether CSP is applicable for adenocarcinomas is still under debate, as heat‐induced cancer cell death cannot be anticipated. Real‐time diagnosis as to whether or not polyps are malignant, and real‐time decision as to whether to use cold or hot snare is thus essential for colonoscopists during routine colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Both adenomas and superficial adenocarcinomas are subject to endoscopic resection. Cold‐snare polypectomy (CSP) is becoming increasingly popular for the resection of adenomas; however, whether CSP is applicable for adenocarcinomas is still under debate, as heat‐induced cancer cell death cannot be anticipated. Real‐time diagnosis as to whether or not polyps are malignant, and real‐time decision as to whether to use cold or hot snare is thus essential for colonoscopists during routine colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Horiuchi et al reported that the rate of arterial injury in the submucosal layer after HSP is as high as 39%, which is a main cause of post‐polypectomy bleeding . Another study found that 60% of hot resections advanced to the deep submucosa and 20% to the muscularis propria, where the vessel diameter was larger and the number of large vessels was greater . More recently, polyp resection without electrocautery, called CSP, has attracted the attention of colonoscopists because of shorter procedure time and low incidence of adverse events, especially post‐polypectomy bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for patients taking antithrombotic agents, cold snare polypectomy may be safer than hot snare polypectomy in relation to delayed bleeding. Other recent studies based on pathological analysis also support the notion that cold snare polypectomy causes less damage to deeper submucosal layers involving more large vessels, resulting in the reduced incidence of hemorrhage after cold snare polypectomy …”
Section: Outcomes Of Cold Snare Polypectomymentioning
confidence: 56%
“…Other recent studies based on pathological analysis also support the notion that cold snare polypectomy causes less damage to deeper submucosal layers involving more large vessels, resulting in the reduced incidence of hemorrhage after cold snare polypectomy. 32,33 Recently, direct oral anticoagulants are commonly used in Japan as well as in western countries. However, patients often stop taking direct oral anticoagulants on the day that they undergo colonoscopy.…”
Section: Delayed Bleeding or Perforationmentioning
confidence: 99%